Assessing benefits and costs of expanded green hydrogen production to facilitate fossil fuel exit in a net-zero transition. (March 2023) - Maynard, Ian; Abdulla, Ahmed
Highlights: Assessments of H2 transition rarely integrate empirical growth or learning rates. We model plausible transition pathways in the Atlantic Maritimes region of Canada. Achieving 2050 targets requires aggressive performance and scaling assumptions. Compound annual growth rates need to meet or exceed 36%. H2 avoids carbon less cost-effectively than direct integration of renewable power. Abstract: Large jurisdictions—including Australia, Canada, the European Union, the United Kingdom, and the United States—are aggressively pursuing a role for hydrogen in the net-zero transition. Past assessments focus on pilot projects or hydrogen hubs and assume cost-competitive hydrogen production by a certain date. Here, we simulate a production facility that couples offshore wind with electrolysis to produce green hydrogen in Canada's Atlantic Maritimes—a region with a size and energy profile similar to other nations', with fossil and nuclear infrastructure that will retire prior to the 2050 net-zero target. We employ growth and learning rates derived from industrial experience and estimate the installed capacity, cost, and emissions of this integrated energy system. Various scenarios are considered, including ones with and without hydrogen storage; one that integrates offshore wind into the grid instead; and one that serves the hydrogen needs of freight transportation. Hydrogen production is at least four times more expensive than grid integration. Projects could only be implemented by 2050 and at <2 $/kgH2 by assuming aggressive growth rates, learning rates, and electrolyzer capital costs of 500 $/kW. This analysis gives policymakers an appreciation of the effort, costs, and emission benefits of producing green hydrogen at scale.